Good education, the good teacher, and a practical art of living a good life: a Catholic perspective. Issue 1 (2nd January 2017) - Hermans, Chris
Abstract: What is good education? We value education for reasons connected to the good provided by education in society. This good is connected to be the pedagogical aim of education. This article distinguishes five criteria for good education based on the concept of 'Bildung'. Next, these five criteria are used to develop the idea of the good teacher. The rationale behind the analysis is that the good teacher should be able to realise what we consider to be good education. There are different traditions of religiously affiliated schools in the world. This article gives insight into the idea of the good teacher in two documents of the Catholic Congregation of Education on the lay teacher. Finally, the article focuses on the formation of a practical art of living a good life. Again, the five characteristics of good education structure the analysis of this type of educational formation.